Recording memories from political conflict : a film-maker's journey - McLaughlin, Cahal (Intellect, 2010)
Based on work the author has carried out with survivor groups in South Africa and Northern Ireland, Recording Memories from Political Violence combines written and audiovisual texts to describe and analyze the use of documentary filmmaking in recording experiences of political conflict. A variety of issues relevant to the genre are addressed at length, including the importance of ethics in the collaboration between the filmmaker and the participant and the effect of location on the accounts of participants. McLaughlin draws on the diverse fields of film and cultural studies, as well as nearly.